SOME ASPECTS OF THE BIOLOGY OF OTOLITHES CUVIERI (TREWA VAS) AND JOHNIUS GLAUCUS (DAY) FROMVERAV AL - RAJE, SADASHIV GOPAL (Journal of Indian Fisheries Association, 2015)
The length-weight relationship in O.cuvieri and J.glaucus can be describedby the equations log W = -5.27997 + 3.13225 log L and log W = -4.93431 + 3.02556logL respectively. The length at first maturity in O.cuvieri is estimated as 256mm and in J.glaucus as 180 mm. Empty stomachs occurred in high percentagein both the species. A study on composition of food items revealed thatO.cuvieri feeds on a variety of organisms while J. glaucus a selective feeder.Key words : Length-weight relationship, food & feeding, maturation,spawning.